Advanced Logic Synthesis (Springer International Publishing, 2018)
This book provides a single-source reference to the state-of-the-art in logic synthesis. Readers will benefit from the authors' expert perspectives on new technologies and logic synthesis, new data structures, big data and logic synthesis, and convergent logic synthesis. The authors describe techniques that will enable readers to take advantage of recent advances in big data techniques and frameworks in order to have better logic synthesis algorithms. Describes how to map logic into new post-CMOS technologies and devices; Explains how to use different types of internal data structures, such as Majority-Inverter-Graphs; Discusses how to mix logic synthesis and physical design in order to have more effective and convergent ways to perform logic synthesis integrated in a complete flow.